Determination of Some Elements in Moss Samples from North Eastern Anatolia, Turkey - Özdemir*, Turan; Apaydin†, Gökhan; Mendil‡, Durali; Numan Bulut§, Volkan; Cengiz†, Erhan; Gündogdu§, Ali; Aylikçi†, Volkan (Asian Journal of Chemistry, 2024)
Nine moss species were collected from high-density traffic roads and near the copper and zinc mine in Çayeli, Turkey. Eleven elements (K, Ca, Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn and Pb) were analyzed using AAS and EDXRF. The metal concentrations in moss samples were found to be 4057-30064, 7275-31658, 313-7595, 25.3-101.6, 121-1252, 18446-65851, 5.3-14.3, 12.4-60.0, 17.4-1442.5, 90-2175 and 15.5-87.5, mg/kg for potassium, calcium, titanium, chromium, manganese, iron, cobalt, nickel, copper, zinc and lead, respectively.